Art reception for people with psychiatric experiences contributions to a receptive art-therapy - Lisa Niederreiter (Arteterapia)
This paper analyses the theoretical foundations of art receptive procedures for people with psychotic illness on the base of the “iconic turn” discourse in recent aesthetic theory. Fundamental axioms (such as the “surplus value” of the picture, its resemblance of reality; the role of the observer in the process of reception) are discussed in realtion to the perceptive changes that accompany psychotic illness. Important correlations are established between the nature of the picture (constancé, protective function, creation of an “other” or “opposite”, reality-detail) and the necesssity to reorganise and restabilise the overpowering effects of psychotic perception in individuals and their contact to reality. The theoretical aspects are discussed with examples of practical work.